2011
DOI: 10.1007/s10646-011-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metal exposure on blood haemoglobin concentration and methemoglobin percentage in Lumbricus terrestris

Abstract: The earthworm haemoglobin (Hb) is a large extracellular hemoprotein flowing in a closed circulatory system. In spite of the fundamental role of this respiratory pigment in earthworm physiology, little is known about its sensitivity to environmental pollutants. The aim of the present work was to investigate the possible effect of heavy metal (cadmium, copper, mercury) exposure on Hb concentration and oxidation state (methemoglobin formation) in the earthworm Lumbricus terrestris. In addition, the tissue concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…They were divided into five subgroups: the first ( n = 30) was utilized as initial control (at time 0), the second ( n = 20) was exposed to copper sulphate, the third ( n = 20) was exposed to cadmium chloride, the fourth ( n = 20) was exposed to a mixture of the two metals, and the fifth was utilized as final control to be analyzed at the end of the exposure experiment. The exposure time was 72 h. As previously demonstrated [35], this time is sufficient to induce a significant response to heavy metal exposure in L. terrestris . The toxicant concentrations utilized were 45 mg/kg of soil for copper sulphate and 1 mg/kg of soil for cadmium chloride, respectively.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…They were divided into five subgroups: the first ( n = 30) was utilized as initial control (at time 0), the second ( n = 20) was exposed to copper sulphate, the third ( n = 20) was exposed to cadmium chloride, the fourth ( n = 20) was exposed to a mixture of the two metals, and the fifth was utilized as final control to be analyzed at the end of the exposure experiment. The exposure time was 72 h. As previously demonstrated [35], this time is sufficient to induce a significant response to heavy metal exposure in L. terrestris . The toxicant concentrations utilized were 45 mg/kg of soil for copper sulphate and 1 mg/kg of soil for cadmium chloride, respectively.…”
Section: Methodsmentioning
confidence: 94%
“…Previous studies demonstrated a significant induction of Mt proteins in different earthworm species such as Lumbricus rubellus , Eisenia fetida , and Eisenia andrei exposed to cadmium [3133] or in Lumbricus mauritii exposed to Pb and Zn contaminated soil [27] and in Lumbricus terrestris exposed to cadmium, copper, and mercury [30, 34, 35]. Morgan et al [8] previously described the immunoperoxidase localization of Mt in the major organs and tissues of the earthworm Lumbricus rubellus sampled from a mine soil heavily polluted with Pb, Zn, and Cd.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of MTs by metal exposure has been detected in a wide variety of organisms including earthworms (Stürzenbaum et al, 2001). For example a significant induction of MT proteins was observed in different earthworm species such as Lumbricus rubellus, Eisenia fetida, Eisenia andrei exposed to cadmium (Calisi et al, 2009;Demuynck et al, 2006;Ndayibagira et al, 2007;Brulle et al, 2007), or in Lumbricus mauritii exposed to Pb and Zn contaminated soil (Maity et al, 2011) and in Lumbriucus terrestris exposed to cadmium, copper and mercury (Calisi et al, 2011a). It is known that earthworms share a high tolerance to heavy metal exposure (Stürzenbaum et al, 1998) also thanks to the fundamental contribution of these metalbinding proteins.…”
Section: Metallothioneinsmentioning
confidence: 99%
“…In spite of the fundamental role of this respiratory pigment in earthworm physiology, little is known about its sensitivity to environmental pollutants. Recently Calisi et al (2011a) demonstrated heavy metal (cadmium, copper, mercury) exposure to significantly induce changes in either Hb concentration or its oxidation state in the earthworm Lumbricus terrestris. Exposure to heavy metals (10 -5 -10 -3 M for Cd, 10 -4 -10 -3 M for Hg, and 10 -4 -10 -2 M for Cu) was found to increase blood Hb concentration.…”
Section: Haemoglobin Oxidationmentioning
confidence: 99%
“…Because of its environmental persistence and ability to be incorporated into food chains, the mercury accumulation in water might be magnified within ecosystems and be potentially hazard to invertebrates and fishes and ultimately jeopardize human health [9,10]. Therefore, knowledge of the toxicity of mercury to aquatic biota is of great importance.…”
Section: Introductionmentioning
confidence: 99%